2018
DOI: 10.1002/cctc.201801023
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Chemical Imaging of a Single Catalyst Particle with Tip‐Enhanced Fluorescence Microscopy

Abstract: Determining the active site in real‐life solid catalysts remains an intellectual challenge and is crucial for exploring the road towards their rational design. In recent years various micro‐spectroscopic methods have revealed valuable structure‐activity data at the level of a single catalyst particle, even under reaction conditions. Herein, we introduce Tip‐Enhanced FLuorescence (TEFL) microscopy as a novel and versatile characterization tool for catalysis research. This has been achieved using a Fluid Catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Therefore, it would be particularly interesting to study how mass transport and reactivity are affected by defects in materials such as MOFs via correlation with material properties and surface topology obtained with atomic force microscopy-infrared microscopy (AFM-IR) and scanning tunneling microscopy (STM). High resolution spectral mapping of the fluorescent reaction products using tip-enhanced fluorescence (TEFL) microscopy could provide additional information about the reaction products formed at high concentration [125]. Such correlative approaches will also be highly beneficial for the study of structure-performance relationships in lessordered materials such as complex heterogeneous catalysts, for example FCC particles and extrudates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would be particularly interesting to study how mass transport and reactivity are affected by defects in materials such as MOFs via correlation with material properties and surface topology obtained with atomic force microscopy-infrared microscopy (AFM-IR) and scanning tunneling microscopy (STM). High resolution spectral mapping of the fluorescent reaction products using tip-enhanced fluorescence (TEFL) microscopy could provide additional information about the reaction products formed at high concentration [125]. Such correlative approaches will also be highly beneficial for the study of structure-performance relationships in lessordered materials such as complex heterogeneous catalysts, for example FCC particles and extrudates.…”
Section: Discussionmentioning
confidence: 99%
“…Although the index of apparent acid strength is certainly influenced by the confinement effects, 53 the exquisite method design in this work makes it possible to reflect the spatial distribution of the intrinsic acid strength by the index of apparent acid strength (details discussion can be found in Supporting Information). This results reveal that the acid strength is nonuniform on the level of HZSM‐5 crystal grains, which can provide an alternate explanation for the observed difference in the catalytic activity of the Brønsted acid sites at different region of a single HZSM‐5 particle according to fluorescence microscope method 40,42‐44 …”
Section: Resultsmentioning
confidence: 83%
“…The correlated ultrastructure‐reactivity information obtained by integration of transmission electron and single‐molecule fluorescence microscopy (SFM‐TEM) confirmed the existence of intrinsic differences in reactivity of the acid sites in different HZSM‐5 crystal particles or even within the same zeolite crystal particle 43 . Very recently, a tip‐enhanced fluorescence microscopy method was developed to provide direct two‐dimensional hyperspectral information (without the complex post process of data required in SFM), and the results also recognized the nonuniform spatial distribution of Brønsted acidity within individual zeolite crystals 44 . Therefore, the investigation of acid distribution on the level of crystal grains is necessary and valuable.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite the advantages of high spatial resolution and rich chemical information offered by TERS, 1,19,20 only a handful of TERS studies of catalytic reactions have been reported so far. 2128 Furthermore, the majority of such studies have been carried out in ambient air or ultrahigh vacuum, with only a few in liquid environments, mostly limited to point spectroscopy measurements. 2934 2D nanoscale chemical imaging of catalytic reactions in liquids represents a key challenge but has not been achieved using TERS, primarily due to the chemical reactivity, 22,35 short lifetime, 3639 and/or instability of TERS probes in liquids.…”
mentioning
confidence: 99%